MEDIA DAN TEKNOLOGI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Cahyadi, Ani; Qutni, Darul; Saifullah, Saifullah (CV. Lafadz Jaya, 2024)
This study aims to explore the use of learning media in the teaching and learning process of Islamic Religious Education (PAI). Learning media is a tool that can facilitate the delivery of material and improve learners' understanding. In the context of PAI, learning media has an important role to visualize abstract concepts and attract students' interest in learning. This research uses a qualitative approach with observation, interview, and documentation study methods. Data were collected from schools that implemented PAI learning media, both visual, audio, and audiovisual media. The results showed that the use of PAI learning media can increase interest in learning, facilitate understanding of the material, and create a more pleasant learning atmosphere. However, there are some obstacles such as limited facilities and infrastructure, as well as teacher competence in using learning media. This study provides recommendations for improving facilities and teacher training in optimizing the use of PAI learning media. The findings of this study contribute to the development of more effective and interesting learning strategies in PAI subjects.